Interactive pop-up book education and preoperative anxiety among school-aged children undergoing general anaesthesia - Shofy Humaira Azzahra; Cahaya Nugraheni; Astika Nur Rohmah (JOURNAL OF Mental Health Concerns, 2026)
Background: Surgical procedures involving general anaesthesia are often unfamiliar experiences for school-aged children (6–12 years), frequently triggering preoperative anxiety. Unresolved anxiety may affect physiological stability and hinder the recovery process. Therefore, innovative educational media that are appropriate to children's developmental stages, such as interactive popup books, are needed to provide visual and engaging explanations of medical procedures and help reduce psychological distress. Purpose: To determine the effect of educational intervention using an interactive pop-up book on preoperative anxiety levels among paediatric patients undergoing general anaesthesia. Method: A pre-experimental design with a one-group pretest–posttest approach. The study sample consisted of 63 respondents selected using a purposive sampling technique. Anxiety levels were measured using the Chinese Version State Anxiety Scale for Children (CSAS-C). Data were analysed using the Wilcoxon Signed Rank Test. Result: Prior to the intervention, the majority of respondents (58.7%) experienced severe anxiety. Following educational intervention through the interactive pop-up book, a significant reduction in anxiety levels was observed, with most respondents classified as having moderate anxiety (57.1%) and mild anxiety (31.7%). Statistical analysis showed a p-value of 0.000 (p < 0.05), indicating a significant effect of the intervention. Conclusion: Preoperative anxiety scores decreased significantly following interactive pop-up book education among school-aged children undergoing general anaesthesia. Controlled studies are needed to confirm the effectiveness of the intervention. Keywords: General Anaesthesia; Pop-Up Book; Preoperative Anxiety; School-Aged Children.